Human Brucellosis Mimicking Axial Spondyloarthritis： a Challenge for Rheumatologists when Applying the 2009 ASAS Criteria - 叶丛 沈桂芬 李守新 董凌莉 余毅恺 凃巍 朱盈姿 胡绍先 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
Although the development of the 2009 Sp A classification criteria by Assessment of Spondylo Arthritis international Society（ASAS） represents an important step towards a better definition of the early disease stage particularly in axial spondyloarthritis（ax Sp A）, the specificity of the criteria has been criticized these days. As the commonest zoonotic infection worldwide, human brucellosis can mimic a large number of diseases, including Sp A. This study was performed to determine the frequency of rheumatologic manifestations in patients with brucellosis and the chance of misdiagnosing them as having ax Sp A in central China. The results showed that clinical manifestations of ax Sp A could be observed in brucellosis. Over half of patients had back pain, and one fifth of the patients with back pain were less than 45 years old at onset and had the symptom for more than 3 months. Two young males were falsely classified as suffering from ax Sp A according to the ASAS criteria, and one with MRI proved sacroiliitis was once given Etanercept for treatment. Therefore, differential diagnosis including human brucellosis should always be kept in mind when applying the ASAS criteria, even in traditionally non-endemic areas.